TORAH TEACHES: "EVERYTHING IS VERY GOOD" - Maller, Allen S. (Journal of Dharma, 2005)
Some people are optimistic and some others are pessimistic. Some are hopeful and positive while some are despairing and negative about life and everything that surrounds it. A basic teaching of Judaism is that optimism, hope, and positive outlook are Mitsvot (Jewish religious duties). The natural world is neither fundamentally a place of suffering, pain, cruelty and sorrow, nor is the human world basically evil: a community filled with lust, violence and greed. Nature is good. Human society or history is improvable. Each individual’s personal world can be good and improvable if he or she makes it so. Here are three examples of Jewish teachings of positive affirmation applied to nature, personal psychology, and a vision of historical development.